The ethnobotany study of Babad Dalan ritual ceremony (BDRC) of Javanese in Gunungkidul, Yogyakarta to biocultural conservation - Silalahi, Marina; Wahyuningtyas, Riska Septia; Kalima , Titi; Situmorang , Agnes Feronika (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
The Babad Dalan ritual ceremony (BDRC) is a ritual ceremony by the local Javanese ethnic community in Gunungkidul which has been carried out for hundreds of years using various types of plants. Biocultural studies of ritual ceremonies as part of biodiversity and cultural conservation are still limited. The purpose of this study is to explain the process of carrying out the ritual and explain the diversity of plants used in BDRC. This study was conducted using an ethnobotanical approach through surveys and semi-structured interviews. Respondents consisted of key informants (5 people) and general respondents (25 people) who were determined by purposive sampling. Data analysis was carried out qualitatively using descriptive statistics. Results: The local Javanese ethnic community in Gunungkidul carries out BDRC every year as a ceremony of gratitude to God for the success of an abundant harvest. A total of fifty-eight species belonging to fifty-one genera and twenty-seven families are used in BDRC which are used as ingredients for offerings, gunungan, and tumpeng. Plants are used as components of gunungan